Zero Single-Use Plastics University - Tatiana Molina Velásquez; Hernán Darío Giraldo (Journal of Sustainability Perspectives, 2021)
Since 2019 CES University began with the implementation of the zero single-use plastics guidelines in order to restrict 100% the use of all single-use plastics at Campus and thus avoid the final disposal in sanitary landfills, with all the negative impact that it has into the fauna, flora and human health, eliminating the generation through prevention, reduction, reuse and recycling. Those single-use plastic products were replaced by elements such as cane bagasse and starch of corn; among others biodegradable and compostable, in order to end the life cycle of these products transforming them into compost. Since the use of single-use plastic elements was banned, we managed to reduce the generation of these products by 89%. From 471.5 Kg in 2018 to 53 Kg in 2019. With this practice, we contribute to SDG 13 - goal 13.3, SDG 12 - goal 12.4 and 12.5. This practice is being replicated in 10 more universities countrywide.